THE INTERVENING ROLE OF E-SATISFACTION IN RELATIONSHIPS BETWEEN E-SERVICE QUALITY AND E-LOYALTY: CASE OF BNI MOBILE BANKING IN INDONESIA - Utomo, Tasya Yesica; Hidayat, Agus Maolana (Universitas Brawijaya, Indonesia, 2023)
Banking as a financial intermediary institution can play a role in encouraging domestic economic growth which can help develop the economy in various regions. Almost all aspects of life today require various kinds of technological assistance which enables the mobility of capital or investment to be easier, faster and more useful for everyday life due to the rapid development of technology and information. The purpose of this study is to determine the response and influence of E-Service Quality on E-loyalty through E-Satisfaction of BNI Mobile Banking user, either directly or indirectly. The research method used is descriptive and quantitative involving 225 respondents using BNI Mobile Banking in Indonesia. The sampling technique used is non-probability sampling with the type of convenience. Data processing and analysis techniques use PLS-SEM through SmartPLS 3.0 software. Quality of electronic services (in terms of effectiveness, compliance, system availability, privacy, contact, and responsiveness) has a direct impact on e-loyalty and e-satisfaction. E-satisfaction has been shown to aid in the creation of client loyalty as a connection between service quality and consumer satisfaction.